"Lost trust in the system": system barriers to publicly available mental health and substance use services for transgender women in San Francisco - Glenda N. Baguso; Karen Aguilar; Sofia Sicro; Malaya Mañacop; Jerry Quintana; Erin C. Wilson (BMC, 2022)
Abstract Background Little is known about the barriers to mental health and substance use services for trans women living with HIV. We conducted a qualitative study with trans women living with HIV and providers to explore barriers to mental health and substance use services in San Francisco. Methods We conducted focus group discussions and key informant interviews with a total of 15 medical, mental health, substance use, and social service providers and trans women living with HIV. We identified, analyzed, and reported themes using thematic analysis and derived themes directly from the data. Results Our study participants identified two main themes and three subthemes. One main theme is that trans women and providers have lost trust in the system due to (a) lack of a linkage system between referrals and services, (b) structural barriers such as service location, language capacity, clinic hours, and (c) constant changes in services available. Another main theme is anti-trans and mental health stigma. Conclusions Interventions to coordinate linkage from medical to mental health and substance use (MHSU) services are urgently needed to facilitate the utilization of MHSU services. Other interventions to improve quality monitoring and system improvement, and to address multiple stigmas broadly in society are needed to improve unmet MHSU service needs among trans women living with HIV in San Francisco.